PENGARUH LATIHAN LOMPAT KOTAK KARDUS TERHADAP HASIL LOMPAT JAUH GAYA JONGKOK SISWA PUTRA KELAS V SD NEGERI 152 PALEMBANG - Lanos, Muhsana El Cintami (STKIP Pasundan, 2019)
The aim of this study was to determine the effect of cardboard box jumping exercises on squat-style long jump results in male students of SD Negeri 152 Palembang. The method in this study is pure experiment (experimental tru). Data obtained from test results were analyzed with data normality, homogeneity tests, and hypothesis testing using t test statistics. The results of data analysis and discussion can be concluded that: the average initial jump pretest squat style test in the experimental group students was 2.23, while the control group was 2.24 while the average final test (posttest) squat style long jump on the experimental group students were 2.51 while the control group was 2.27 and the results of testing the hypotheses obtained tcount> ttable or 17.5> 1.68 this meant that the hypothesis that there was an influence of the cardboard box jump training on the results of the long jump in class V male students The truth of Palembang 152 Public Elementary School is acceptable